Cities, sagebrush, and solitude : urbanization and cultural conflict in the Great Basin - Witt, Stephanie L.; Judd, Dennis R. (The urban West series, 2014)
"This manuscript explores the environmental consequences and political conflicts arising from the urbanization of the Great Basin. It focuses on four major metropolitan areas on the Basin's rim--Boise, Reno, Salt Lake City, and Las Vegas--to explore how these cities cope with the problems associated with rapid growth, when attempts to do so provoke conflict between urban residents and the people who live in the thinly populated desert outback. In the Basin, policies to address the environmental and resource limitations imposed by the desert may be incompatible with a rural political culture that resists all cooperation or governmental effort. Each chapter of the manuscript traces the way that the tensions between three ingredients--cities, remarkable scarcity, and a conservative political culture--inform contemporary policy debates and public policies of the region through an analysis of the environmental stresses connected to economic change, resource extraction, land management, and urban development"--